Yield, Quality, and Antioxidant Activity of Clove (Syzygium aromaticum L.) Bud Oil at the Different Phenological Stages in Young and Mature Trees - Faisal Nur Alfikri; Rini Pujiarti; Mochamat Gunawan Wibisono; Eko Bhakti Hardiyanto (Scientifica)
Buds and flowers of clove (Syzygium aromaticum L.) are economically important essential oil sources. The purpose of this study was to assess the yield, quality, and antioxidant activity of Zanzibar clove bud oil between three phenological stages (budding-3, full-budding, and flowering) in young (3-4 years) and mature trees (45 years). Chemical compositions of the oil were analyzed using GC-MS, and the physicochemical properties were measured based on SNI 06-4267-1996. Antioxidant activity was analyzed using the DPPH method. The results showed flowering buds of young trees produced higher yield (16.73%) than that of the mature ones (14.93%). The GC-MS analysis showed that the main bioactive compound of clove oil was eugenol (68.05–82.38%), which is highest at the flowering stage in mature trees. Almost all of the clove bud oils met physicochemical properties standard required by the SNI 06-4267-1996. DPPH scavenging activity IC50 ranged 15.80–108.85 µg/mL, with the highest antioxidant activity at the flowering stage of young trees. The results indicate that clove at flowering stage produced the best essential oil ingredient, as well as the most efficient source of natural antioxidants with slight differences in quality between the young and mature trees.